A preliminary investigation into the effect of yoga practice on mindfulness and flow in elite youth swimmers - Briegel-Jones, R. M. H.; Knowles, Z.; Eubank, M. R.; Giannoulatos, K.; Elliot, D. (The Sport Psychologist, 2013)
Research has indicated positive effects of mindfulness training as a performance-based intervention and of yoga on mindfulness. This study examined the effects of a 10-week yoga intervention on mindfulness and dispositional flow of elite youth swimmers using a mixed methods design. No significant changes in mindfulness and dispositional flow were identified. Qualitative data suggested that the 10-week yoga intervention had a positive impact on a range of physiological, cognitive, and performance parameters that included elements of mindfulness and flow. Methodological considerations for future research are discussed.